Polymer-Supported Stereoselective Synthesis of Tetrahydrobenzopyrazino-thiadiazinone Dioxides via N-Sulfonyl Iminiums - Cankarova, Nadezda (2014)
The stereoselective synthesis of 1,2,11,11atetrahydrobenzo[e]pyrazino[1,2-b][1,2,4]thiadiazin-3(4H)- one 6,6-dioxides on a solid support via tandem N-sulfonyl iminium ion cyclization, followed by nucleophilic addition is reported. The synthesis proceeded with full control of stereoselectivity at the newly formed asymmetric carbon, under mild conditions, and using commercially available building blocks. The synthetic route provided high-purity crude products